2008
DOI: 10.1108/00483480810906874
|View full text |Cite
|
Sign up to set email alerts
|

Developing a framework for assessing effective development activities

Abstract: Almuth is a lecturer in occupational psychology at Surrey University. Her research areas are training and development including coaching and feedback, the interface of work and non/work and the application of psychometrics in organization, as well as their cross-cultural adaptation. She regularly advises organizations on the design and implementation of staff assessment and development and work/life balance initiatives. Christopher Mabey Research and practical implications:We propose that our classification f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 49 publications
0
11
0
2
Order By: Relevance
“…Several of these are positioned at the organisational level; examples are Human Resource Development orientated approaches (Thomson et al, 1998), the learning organisation (Senge, 2006) or Human Capital Theory (Davenport, 1999, a commonality between these models being that outcomes are often concerned with the enhancement of performance. Other development approaches consider individual differences and motivation such as theories of managerial competence (Boyatzis 1982;2008), the effects of feedback (Ilgen et al, 1979;Kluger and DeNisi 1996) and factors influencing participation in development activities ( Maurer et al 2002b;Maurer and Tarulli, 1994).…”
Section: Differences Between Training and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of these are positioned at the organisational level; examples are Human Resource Development orientated approaches (Thomson et al, 1998), the learning organisation (Senge, 2006) or Human Capital Theory (Davenport, 1999, a commonality between these models being that outcomes are often concerned with the enhancement of performance. Other development approaches consider individual differences and motivation such as theories of managerial competence (Boyatzis 1982;2008), the effects of feedback (Ilgen et al, 1979;Kluger and DeNisi 1996) and factors influencing participation in development activities ( Maurer et al 2002b;Maurer and Tarulli, 1994).…”
Section: Differences Between Training and Developmentmentioning
confidence: 99%
“…Maurer et al, 2003). A continuously changing work environment has made cyclical training necessary (Buckley and Caple, 2007), on-the-job training being considered most effective, only a fifth of UK managers believing that formal courses are the most effective method (Chartered Institute of Personnel and Development, Mabey, 2008), may or may not entail an explicit career relevant element and may or may not be formally planned and agreed (Rowold and Kauffeld, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Par ailleurs, les activités de développement qui s'arriment aux pratiques de gestion de la performance comme la rétroaction multisource (360 degrés) ou les centres de développement sont surtout ponctuelles et orientées sur une fonction de diagnostic et d'évaluation (McDowall et Mabey, 2008…”
Section: Ce Que L'on Sait Sur L'arrimage De La Gestion De La Performaunclassified
“…They concluded that evaluation of 360° performance is a simple practical solution that can provide valuable information for senior managers of the organization. McDowall and Mabey (2008) surveyed four different functions of growth evaluation, leadership, 360° feedback and central expansion. They concluded that categorizing of the evaluation approaches contains defect because the expansion form of such functions had shown dependency upon the relationship between their managers and authorities.…”
Section: Introductionmentioning
confidence: 99%